A graphite negative electrode composite material and preparation method thereof and lithium ion battery

By generating micropores and nanopores on the surface of graphite negative electrode material, doping conductive carbon material, and depositing porous oxide coating on the outer layer, the problem of poor charging and discharging capacity of existing graphite negative electrode materials under high current density is solved. Achieve higher fast charging performance and first-time charge and discharge efficiency.

CN115207304BActive Publication Date: 2025-02-14SVOLT ENERGY TECHNOLOGY CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202210540469.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-05-17
Publication Date
2025-02-14
Estimated Expiration
2042-05-17

AI Technical Summary

Technical Problem

The existing graphite negative electrode materials have poor charging and discharging capabilities under high current density and are relatively low for the first time, which affects the improvement of energy density and fast charging performance of lithium-ion batteries.

Method used

By generating micropores and nanopores on the surface of graphite negative electrode material, doping conductive carbon material, and depositing porous oxide coatings on the outer layer, the diffusion rate of lithium ions and the electrochemical performance of the battery are improved.

Benefits of technology

The fast charging performance, first charging and discharging efficiency, rate performance and high temperature performance of graphite negative electrode composite materials are improved, and the overall performance of lithium-ion batteries is enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115207304B_ABST
    Figure CN115207304B_ABST
Patent Text Reader

Abstract

The present invention provides a graphite negative electrode composite material, a preparation method thereof and a lithium ion battery. The graphite negative electrode composite material comprises porous graphite doped with a conductive carbon material and a coating layer located on the surface thereof; the coating layer comprises a porous oxide layer; based on the total mass of the graphite negative electrode composite material being 100%, the mass percentage of the coating layer is 1-10%. The present invention improves the fast charging performance of the battery by oxidizing the surface of the graphite material to form pores and growing a conductive carbon material, and deposits a porous oxide shell layer on its outer surface to improve the initial efficiency of the lithium ion battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of negative electrode materials, and in particular relates to a graphite negative electrode composite material and a preparation method thereof, and a lithium ion battery. Background Art

[0002] As the demand for energy density and fast charging performance of lithium-ion batteries continues to increase, the negative electrode materials of lithium-ion batteries need to have high energy density while also improving their fast charging performance accordingly. Currently, commercial negative electrode materials are mainly artificial graphite, with a theoretical specific capacity of 372mAh / g. It has the disadvantages of low energy density and long layered structure insertion and extraction paths, so that its fast charging performance can only meet the charging capacity of low current density (≤4C), and the EOL full charge expansion is about 35%. At the same time, the first efficiency is only between 92% and 94%. The above factors cause the negative electrode material to have slightly poor charging and discharging capabilities at high current density, and the first efficiency deviation, which in turn affects the energy density improvement of the whole battery and its fast charging performance.

[0003] In recent years, one method to improve the fast charging performance of graphite materials is to modify the surface of the graphite material to increase the diffusion rate of lithium ions on the surface. However, since the surface is not activated, there are fewer active sites on the surface of the material, which affects the diffusion rate of lithium ions during its charging and discharging process. Another method to improve the fast charging performance of the material is to perform pore-forming treatment on the surface of the graphite material. The generation of more micropores can increase the insertion and extraction rate of lithium ions to improve the rate performance of the battery. At the same time, the specific surface area of ​​the material is controlled to improve the initial efficiency of the battery.

[0004] Therefore, in this field, there is an urgent need to develop a graphite negative electrode material, which not only has more active sites and certain pores, but also can improve the diffusion rate of lithium ions and the electrochemical performance of the battery. Summary of the invention

[0005] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a graphite negative electrode composite material and a preparation method thereof and a lithium ion battery. The present invention improves the fast charging performance of the battery by oxidizing the surface of the graphite negative electrode material to form pores and growing a conductive carbon material, and deposits a porous oxide coating layer on its outer surface to improve the initial efficiency of the lithium ion battery.

[0006] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0007] In a first aspect, the present invention provides a graphite negative electrode composite material having a core-shell structure, wherein the graphite negative electrode composite material comprises porous graphite doped with a conductive carbon material and a coating layer located on the surface thereof;

[0008] The coating layer comprises a porous oxide layer;

[0009] Taking the total mass of the graphite negative electrode composite material as 100%, the mass percentage of the coating layer is 1-10%.

[0010] In the present invention, the mass percentage of the coating layer in the graphite negative electrode composite material is 1-10%, for example, it can be 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%.

[0011] The present invention generates more micropores and nanopores on the surface of the graphite negative electrode material to increase the storage space of lithium ions, and deposits conductive carbon materials in the pores and on the surface to improve its conductivity. At the same time, the porous oxide in the outer layer forms porous lithium aluminate during the first charge and discharge process, thereby increasing the insertion and extraction rate of lithium ions and improving the first charge and discharge efficiency, rate performance and high temperature performance of the graphite negative electrode composite material.

[0012] In the present invention, the mass percentage of the coating layer in the graphite negative electrode composite material is adjusted to improve the fast charging performance and low temperature performance. If the content is too low, the improvement will be small, and vice versa, the high temperature performance will be too poor.

[0013] Preferably, based on the total mass of the graphite negative electrode composite material as 100%, the mass percentage of the coating layer is 2-3%, for example, it can be 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, or 3%.

[0014] Preferably, the conductive carbon material includes carbon nanotubes, conductive carbon black or graphene.

[0015] Preferably, based on the total mass of the graphite negative electrode composite material as 100%, the mass percentage of the conductive carbon material is 1-10%, for example, it can be 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, and further preferably 1.5-2.5%, for example, it can be 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%.

[0016] In the present invention, the mass percentage of the conductive carbon material is adjusted to 1-10% to improve the dynamic performance. If the content is too low, the improvement will not be obvious, and vice versa, the energy density will be reduced.

[0017] Preferably, the porous oxide layer is a porous aluminum oxide layer.

[0018] Preferably, the porosity of the coating layer is 5-50%, for example, it can be 5%, 8%, 10%, 12%, 15%, 18%, 20%, 22%, 25%, 28%, 30%, 32%, 35%, 38%, 40%, 42%, 45%, 48%, 50%, and more preferably 15-25%.

[0019] In the present invention, the porosity of the coating layer is adjusted to improve the fast charging performance and liquid retention performance of the coating layer. If the porosity is too low, the dynamic performance will not be significantly improved and the impedance will be too large. Otherwise, the energy density will be reduced.

[0020] In a second aspect, the present invention provides a method for preparing the graphite negative electrode composite material according to the first aspect, the method comprising the following steps:

[0021] (1) mixing a graphite negative electrode material and an oxidant, and drying to obtain a graphite negative electrode material A;

[0022] (2) dispersing the graphite negative electrode material A obtained in step (1) and the catalyst solution, spray drying and crushing to obtain a graphite negative electrode material B;

[0023] (3) calcining the graphite negative electrode material B and the carbon source to obtain porous graphite doped with a conductive carbon material, and then depositing porous oxide on the surface of the porous graphite to obtain the graphite negative electrode composite material.

[0024] In the present invention, the surface of the graphite negative electrode material is micro-oxidized to generate more micropores and nanopores, and then added to the catalyst solution for immersion, and carbon nanotubes are grown by vapor deposition method using this as a matrix, and then porous alumina material is deposited on its outer layer by atomic vapor deposition method. The composite material prepared by it generates more micropores and nanopores on the surface of the graphite negative electrode material, increases the storage space of lithium ions, and deposits carbon nanotubes in the pores and on its surface to improve its conductivity. At the same time, the porous alumina on the outer layer forms porous lithium aluminate during the first charge and discharge process, which improves the insertion and extraction rate of lithium ions, and improves the first efficiency, rate performance and high temperature performance of the composite material.

[0025] Preferably, the graphite negative electrode material in step (1) comprises any one of spherical natural graphite, flake graphite or artificial graphite, or a combination of at least two of them.

[0026] Preferably, the average particle size of the graphite negative electrode material in step (1) is 6-15 μm, for example, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, or 15 μm.

[0027] In the present invention, the average particle size of the graphite negative electrode material is adjusted to take into account both the fast charging performance and its energy density. If the particle size is too small, the energy density will be too low and the high temperature performance will be poor. Conversely, the fast charging performance will deteriorate.

[0028] Preferably, the oxidant in step (1) comprises any one of nitric acid, sulfuric acid, potassium permanganate or hydrogen peroxide, or a combination of at least two thereof.

[0029] Preferably, the mass concentration of the oxidant in step (1) is 1-10%, for example, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%.

[0030] In the present invention, the mass concentration of the oxidant in step (1) is adjusted to improve the kinetic performance. If the content is too low, the kinetic performance will not be improved much, and vice versa, the high-temperature performance will be too poor.

[0031] Preferably, the mixing in step (1) is performed under stirring.

[0032] Preferably, the stirring temperature is 25-100°C, for example, 25°C, 30°C, 35°C, 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C, or 100°C.

[0033] Preferably, the stirring time is 12-72 h, for example, it can be 12 h, 16 h, 18 h, 20 h, 22 h, 24 h, 26 h, 30 h, 35 h, 40 h, 45 h, 50 h, 55 h, 60 h, 65 h, 70 h, or 72 h.

[0034] Preferably, the drying in step (1) includes a washing step with deionized water.

[0035] Preferably, the catalyst in the catalyst solution in step (2) comprises any one of ferric nitrate, nickel nitrate, cobalt nitrate, ferric chloride, nickel chloride or cobalt chloride, or a combination of at least two thereof.

[0036] Preferably, the mass concentration of the catalyst solution in step (2) is 1-10%, for example, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%.

[0037] In the present invention, the mass concentration of the catalyst solution in step (2) is adjusted to improve the reaction process of the material and to deposit amorphous carbon as a matrix. If the content is too low, the impedance reduction will not be obvious, and vice versa, the initial efficiency will be reduced.

[0038] Preferably, the mass ratio of the graphite negative electrode material A to the catalyst in step (2) is 100:(0.5-2), for example, it can be 100:0.5, 100:0.52, 100:0.55, 100:0.58, 100:0.6, 100:0.62, 100:0.65, 100:0.7, 100:0.72, 100:0.75, 100:0.8, 100:0.85, 100:0.9, 100:0.95, 100:1, 100:1.1, 100:1.2, 100:1.3, 100:1.4, 100:1.5, 100:1.6, 100:1.7, 100:1.8, 100:1.9, 100:2.

[0039] In the present invention, the mass ratio of the graphite negative electrode material A and the catalyst in step (2) is adjusted to increase the carbon coating amount of the material. If the mass ratio is too low, the impedance reduction will not be obvious, otherwise the first efficiency will be reduced.

[0040] Preferably, the spray drying temperature in step (2) is 200-300°C, for example, 200°C, 210°C, 220°C, 230°C, 240°C, 250°C, 260°C, 270°C, 280°C, 290°C, or 300°C.

[0041] Preferably, the spray drying pressure in step (2) is 0.1-0.3 MPa, for example, it can be 0.1 MPa, 0.12 MPa, 0.15 MPa, 0.18 MPa, 0.2 MPa, 0.22 MPa, 0.25 MPa, 0.28 MPa, or 0.3 MPa.

[0042] Preferably, the carbon source in step (3) comprises any one of methane, acetylene, ethylene or ethane, or a combination of at least two thereof.

[0043] Preferably, the calcination in step (3) is carried out in an inert atmosphere.

[0044] Preferably, the calcination temperature in step (3) is 700-1000°C, for example, it can be 700°C, 720°C, 750°C, 780°C, 800°C, 820°C, 850°C, 880°C, 900°C, 920°C, 950°C, 980°C, or 1000°C.

[0045] Preferably, the calcination time in step (3) is 1-6 h, for example, 1 h, 2 h, 3 h, 4 h, 5 h, or 6 h.

[0046] Preferably, the deposition in step (3) is atomic vapor deposition.

[0047] In the present invention, atomic vapor deposition has the advantages of uniform deposition, high density, low energy density of the battery, and improved fast charging and cycle performance.

[0048] In a third aspect, the present invention provides a lithium-ion battery, comprising a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein the negative electrode sheet comprises the graphite negative electrode composite material described in the first aspect.

[0049] Compared with the prior art, the present invention has the following beneficial effects:

[0050] (1) The present invention provides a graphite negative electrode composite material, which is prepared by doping a catalyst in porous graphite and using it as a matrix to grow carbon nanotubes on its surface. The porous structure and the conductive carbon material with high conductivity grown thereon are used to reduce the electronic impedance and increase the ionic conductivity, thereby improving the fast charging performance of the battery.

[0051] (2) A porous oxide shell is deposited on the outer layer of the porous graphite core by the atomic vapor growth method. Due to the inertness of the reaction between the oxide and the electrolyte, the lithium ions consumed in the formation of the solid electrolyte membrane during the charging and discharging process are reduced, thereby improving the initial efficiency of the battery. At the same time, compared with the traditional solid / liquid coating method, the atomic vapor deposition method has the advantages of high density and high consistency. While being able to improve the initial efficiency of the material, due to the small amount of oxide coating (≤1%), it has little effect on the energy density and can improve the initial efficiency of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0052] Figure 1 This is a 1000x SEM image of the graphite negative electrode composite material prepared in Example 1;

[0053] Figure 2 This is a 3000x SEM image of the graphite negative electrode composite material prepared in Example 1. DETAILED DESCRIPTION

[0054] The technical solution of the present invention is further described below by combining the accompanying drawings and specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0055] Example 1

[0056] This embodiment provides a graphite negative electrode composite material with a core-shell structure, the graphite negative electrode composite material includes porous graphite doped with carbon nanotubes and a porous aluminum oxide layer located on the surface thereof. The mass percentage of the porous aluminum oxide layer (porosity of 30%) in the graphite negative electrode composite material is 5%, and the mass percentage of the carbon nanotubes is 2%).

[0057] The preparation method of the graphite negative electrode composite material is as follows:

[0058] (1) 100 g of artificial graphite negative electrode material was immersed in 1000 mL of nitric acid oxidant with a mass concentration of 5%, and stirred and oxidized at a temperature of 60° C. for 24 h, and then dried for standby use after deionized water treatment to obtain a graphite negative electrode material A with a slightly oxidized surface;

[0059] (2) adding 1 g of ferric nitrate to 50 mL of deionized water to prepare a catalyst solution with a mass concentration of 2%, adding the graphite negative electrode material A obtained in step (1) to disperse evenly, spray drying (temperature of 250° C., pressure of 0.2 MPa) and crushing to obtain graphite negative electrode material B;

[0060] (3) Calcine the graphite negative electrode material B and methane at 800°C for 3h to obtain porous graphite doped with conductive carbon material, and then atomically vapor deposit porous oxide on the surface of the porous graphite, wherein the specific deposition parameters are as follows: introduce porous alumina for 0.5 seconds; purge with nitrogen for 60 seconds; introduce an oxygen source for 5 seconds; purge with nitrogen for 5 seconds; introduce water for 0.03 seconds; purge with nitrogen for 50 seconds; and cycle 20 times starting from introducing porous alumina for 0.5 seconds to form a porous alumina deposition layer of uniform thickness layer by layer, and cool to room temperature after completing the cyclic deposition to obtain the graphite negative electrode composite material.

[0061] from Figure 1 It can be seen that the prepared graphite negative electrode composite material is granular with uniform size distribution, and its particle size is between 8 and 15 μm. Figure 2 It shows that the amorphous carbon on the surface of the material is wrinkled.

[0062] Example 2

[0063] This embodiment provides a graphite negative electrode composite material with a core-shell structure, wherein the graphite negative electrode composite material comprises porous graphite doped with carbon nanotubes and a porous alumina layer on its surface. The mass percentage of the porous alumina layer (porosity of 5%) in the graphite negative electrode composite material is 10%, and the mass percentage of the carbon nanotubes is 1%).

[0064] The preparation method of the graphite negative electrode composite material is as follows:

[0065] (1) 100 g of artificial graphite negative electrode material was immersed in 1000 mL of nitric acid oxidant with a mass concentration of 5%, and stirred and oxidized at a temperature of 60° C. for 24 h, and then dried for standby use after deionized water treatment to obtain a graphite negative electrode material A with a slightly oxidized surface;

[0066] (2) adding 1 g of ferric nitrate to 50 mL of deionized water to prepare a catalyst solution with a mass concentration of 2%, adding the graphite negative electrode material A obtained in step (1) to disperse evenly, spray drying (temperature of 200° C., pressure of 0.3 MPa) and crushing to obtain graphite negative electrode material B;

[0067] (3) Calcine the graphite negative electrode material B and methane at 800°C for 3h to obtain porous graphite doped with conductive carbon material, and then atomically vapor deposit porous oxide on the surface of the porous graphite, wherein the specific deposition parameters are as follows: introduce porous alumina for 0.5 seconds; purge with nitrogen for 60 seconds; introduce an oxygen source for 5 seconds; purge with nitrogen for 5 seconds; introduce water for 0.03 seconds; purge with nitrogen for 50 seconds; and start from introducing porous alumina for 0.5 seconds and cycle for 50 times to form a porous alumina deposition layer of uniform thickness layer by layer, and after completion of the cyclic deposition, cool to room temperature to obtain the graphite negative electrode composite material.

[0068] Example 3

[0069] This embodiment provides a graphite negative electrode composite material with a core-shell structure, wherein the graphite negative electrode composite material comprises porous graphite doped with carbon nanotubes and a porous alumina layer on its surface. The mass percentage of the porous alumina layer (porosity of 25%) in the graphite negative electrode composite material is 1%, and the mass percentage of the carbon nanotubes is 10%).

[0070] The preparation method of the graphite negative electrode composite material is as follows:

[0071] (1) 100 g of artificial graphite negative electrode material was immersed in 1000 mL of sulfuric acid oxidant with a mass concentration of 1%, and stirred and oxidized at a temperature of 25° C. for 72 h, and then dried for use after deionized water treatment to obtain a graphite negative electrode material A with a slightly oxidized surface;

[0072] (2) adding 0.5 g of ferric chloride to 50 mL of deionized water to prepare a catalyst solution with a mass concentration of 1%, adding the graphite negative electrode material A obtained in step (1) to disperse evenly, spray drying (temperature of 300° C., pressure of 0.1 MPa) and crushing to obtain graphite negative electrode material B;

[0073] (3) Calcine the graphite negative electrode material B and acetylene at 700°C for 6 hours to obtain porous graphite doped with a conductive carbon material, and then atomically vapor deposit a porous oxide on the surface of the porous graphite, wherein the specific deposition parameters are as follows: introduce porous alumina for 0.5 seconds; purge with nitrogen for 60 seconds; introduce an oxygen source for 5 seconds; purge with nitrogen for 5 seconds; introduce water for 0.03 seconds; purge with nitrogen for 50 seconds; and cycle 10 times starting from introducing the porous alumina for 0.5 seconds to form a porous alumina deposition layer of uniform thickness layer by layer, and after completion of the cyclic deposition, cool to room temperature to obtain the graphite negative electrode composite material.

[0074] Example 4

[0075] This embodiment provides a graphite negative electrode composite material with a core-shell structure, the graphite negative electrode composite material includes porous graphite doped with carbon nanotubes and a porous aluminum oxide layer located on the surface thereof. The mass percentage of the porous aluminum oxide layer (porosity of 30%) in the graphite negative electrode composite material is 5%, and the mass percentage of the carbon nanotubes is 2%).

[0076] The preparation method of the graphite negative electrode composite material is as follows:

[0077] (1) 100 g of artificial graphite negative electrode material was immersed in 1000 mL of potassium permanganate solution with a mass concentration of 10%, and stirred and oxidized at a temperature of 100° C. for 12 h, and then dried for standby use after deionized water treatment to obtain a graphite negative electrode material A with a slightly oxidized surface;

[0078] (2) adding 2 g of cobalt chloride to 20 mL of deionized water to prepare a cobalt chloride solution with a mass concentration of 10%, adding the graphite negative electrode material A obtained in step (1) to disperse evenly, spray drying (temperature of 250°C, pressure of 0.2 MPa) and crushing to obtain graphite negative electrode material B;

[0079] (3) Calcine the graphite negative electrode material B and ethane at 1000°C for 1 hour to obtain porous graphite doped with conductive carbon material, and then atomically vapor deposit porous oxide on the surface of the porous graphite, wherein the specific deposition parameters are as follows: introduce porous alumina for 0.5 seconds; purge with nitrogen for 60 seconds; introduce an oxygen source for 5 seconds; purge with nitrogen for 5 seconds; introduce water for 0.03 seconds; purge with nitrogen for 50 seconds; and cycle 100 times starting from introducing porous alumina for 0.5 seconds to form a porous alumina deposition layer of uniform thickness layer by layer, and cool to room temperature after completing the cyclic deposition to obtain the graphite negative electrode composite material.

[0080] Example 5

[0081] The difference between this embodiment and embodiment 1 is that the porosity of the porous alumina layer in the graphite negative electrode composite material is 1%, and the rest is the same as embodiment 1.

[0082] Example 6

[0083] The difference between this embodiment and embodiment 1 is that the porosity of the porous alumina layer in the graphite negative electrode composite material is 55%, and the rest is the same as embodiment 1.

[0084] Example 7

[0085] The difference between this embodiment and embodiment 1 is that, based on the total mass of the graphite negative electrode composite material being 100%, the mass percentage of the carbon nanotubes is 0.5%, and the rest is the same as embodiment 1.

[0086] Example 8

[0087] The difference between this embodiment and embodiment 1 is that, based on the total mass of the graphite negative electrode composite material being 100%, the mass percentage of the carbon nanotubes is 15%, and the rest is the same as embodiment 1.

[0088] Comparative Example 1

[0089] This comparative example provides a graphite negative electrode composite material, and the preparation method is as follows:

[0090] 100g of artificial graphite, 1g of carbon nanotube powder and 5g of asphalt were added to a ball mill and dispersed at a dispersion rate of 300rpm for 24h. Then, they were transferred to a tubular furnace and heated to 200℃ for 1h under an argon atmosphere, then heated to 800℃ for 3h. Then, they were cooled to room temperature under an argon atmosphere and crushed to obtain a graphite negative electrode composite material.

[0091] Comparative Example 2

[0092] This comparative example provides a graphite negative electrode composite material, and the preparation method is as follows:

[0093] By atomic vapor deposition, according to the following process: porous alumina for 0.5 seconds; nitrogen purge for 60 seconds; introduction of oxygen source for 5 seconds; nitrogen purge for 5 seconds; introduction of water for 0.03 seconds; nitrogen purge for 50 seconds; 100 cycles starting from the introduction of porous alumina for 0.5 seconds; forming a porous alumina deposition layer of uniform thickness layer by layer on the surface of artificial graphite, cooling to room temperature after completion of the cyclic deposition, and obtaining a porous alumina-coated artificial graphite negative electrode composite material.

[0094] Comparative Example 3

[0095] The difference between this comparative example and Example 1 is that step (3) is not performed, and the rest is the same as Example 1.

[0096] Comparative Example 4

[0097] The difference between this comparative example and Example 1 is that step (2) is not performed, and only steps (1) and (3) are performed, and the rest are the same as Example 1.

[0098] Comparative Example 5

[0099] The difference between this comparative example and Example 1 is that the mass percentage of the porous aluminum oxide layer in the graphite negative electrode composite material is 0.5%, and the other contents are the same as those in Example 1.

[0100] Comparative Example 6

[0101] The difference between this comparative example and Example 1 is that the mass percentage of the porous aluminum oxide layer in the graphite negative electrode composite material is 15%, and the other contents are the same as those in Example 1.

[0102] Application Examples 1 to 8 and Comparative Application Examples 1 to 6

[0103] The graphite negative electrode composite materials provided in Examples 1 to 8 and Comparative Examples 1 to 6 are used to prepare lithium-ion batteries, and the preparation method is as follows:

[0104] The graphite negative electrode composite material is assembled into a button battery. The assembly method is as follows: in a glove box filled with argon, a binder, a conductive agent and a solvent are added to the negative electrode material, stirred to make a slurry, coated on a copper foil, and dried and rolled to obtain a negative electrode sheet. The binder used is LA132 binder, the conductive agent is Super P, the negative electrode material is the graphite negative electrode composite material provided in the embodiment and the comparative example, and the solvent is double distilled water. The proportion of each component is: negative electrode material: Super P: LA132: double distilled water = 95g: 1g: 4g: 220mL; the electrolyte is LiPF6 / EC+DEC (the concentration of LiPF6 is 1.2mol / L, and the volume ratio of EC and DEC is 1:1), the metal lithium sheet is the counter electrode, and the diaphragm is polyethylene, polypropylene or polyethylene propylene composite diaphragm.

[0105] Test conditions

[0106] The graphite negative electrode composite materials provided in Examples 1 to 8 and Comparative Examples 1 to 6 were tested, and the test method was as follows:

[0107] (1) Morphology characterization: The morphology of the obtained graphite negative electrode composite material was characterized by scanning electron microscopy;

[0108] (2) Conductivity test: The powder is pressed into a block structure and the conductivity is tested using a four-probe tester;

[0109] (3) Compacted density test: Weigh a certain mass of powder and place it in a mold (10 mm) and press it with a pressure of 2 T (using a powder compaction density meter, place 1 g of powder in a fixed kettle and press it with a pressure of 2 T, let it stand for 10 seconds, then calculate the height change h (mm) under pressing, and calculate the compacted density, the formula is as follows), calculate the compacted density of the powder:

[0110] Powder compaction density = 1×1000 / (π×5×5×h)

[0111] The lithium-ion batteries provided in Application Examples 1 to 8 and Comparative Application Examples 1 to 6 were tested, and the testing method was as follows:

[0112] (1) Rate performance test: The electrochemical performance test was carried out on a Wuhan Blue Electric CT2001A battery tester, with a charge and discharge voltage range of 0.005V to 2.0V and a charge and discharge rate of 0.1C. At the same time, the specific capacity of the material at a rate of 2C was tested, and the rate performance (2C / 0.1C) was calculated;

[0113] (2) Liquid absorption and retention test: Take the above negative electrode sheet at the same time, use a 1mL burette, and absorb the electrolyte VmL, add a drop on the surface of the electrode sheet, and count until the electrolyte is completely absorbed, record the time t, and calculate the liquid absorption rate V / t of the electrode sheet. The test results are shown in Table 2;

[0114] (3) Soft pack battery test: The graphite negative electrode composite material is used as the negative electrode material to prepare the negative electrode sheet. 1 / 3 Co 1 / 3 Mn 1 / 3 O2) as the positive electrode, LiPF6 solution (solvent is EC+DEC, volume ratio is 1:1, LiPF6 concentration is 1.3 mol / L) as the electrolyte, and celegard2400 as the separator, and 2Ah soft-pack batteries are prepared in sequence, and then the cycle performance and rate performance of the soft-pack batteries are tested.

[0115] Rate performance test conditions: charging rate is 1C / 2C / 3C / 5C, discharging rate is 1C; voltage range: 2.8-4.2V.

[0116] Cycle test conditions: current density is 1C / 1C, voltage range: 2.8-4.2V, temperature: 25±3℃, and cycle number is 500 cycles.

[0117] The test results are shown in Table 1-Table 3:

[0118] Table 1

[0119]

[0120]

[0121] It can be seen from Table 1 that the resistivity of the graphite negative electrode composite powders prepared in Examples 1-4 is significantly lower than that of the comparative examples. The reason is that the surface coating of aluminum oxide can not only increase the compaction density of the material, but also the porous graphite doped with carbon nanotubes can also increase the electronic conductivity of the material, and the porous structure can increase the specific surface area of ​​the material.

[0122] Compared with Example 1, Examples 5-6 are cases where the porosity of the porous alumina layer exceeds the range, and their comprehensive performance is not as good as Example 1; Examples 7-8 are cases where the mass percentage content of carbon nanotubes of the conductive carbon material exceeds the range, and their comprehensive performance is also not as good as Example 1.

[0123] Table 2

[0124]

[0125]

[0126] It can be seen from Table 2 that the first discharge capacity, first charge and discharge efficiency and liquid absorption capacity of the lithium ion battery prepared by using the graphite composite negative electrode material obtained in Examples 1-4 are significantly higher than those in the comparative example. The reason is that the graphite negative electrode composite material in the example has a higher specific surface area, which can improve the liquid absorption performance of the electrode piece, and the outer layer is deposited with porous alumina by atomic vapor phase technology, which can improve the first efficiency and rate performance of the material.

[0127] Table 3

[0128]

[0129] It can be seen from Table 3 that the soft-pack battery prepared by the graphite negative electrode composite material prepared in Examples 1-4 of the present invention has a better constant current ratio. The constant current ratio of the soft-pack battery in the comparative example is significantly reduced because the porous alumina with lithium ion conductivity coated on the surface of the material can improve the ion transmission rate, and the core doped with carbon nanotubes can improve the electron transmission rate of the material, thereby improving the rate performance of the battery. At the same time, the porous alumina in the outer shell has the characteristics of low side reactions, thereby improving the cycle performance of the material.

[0130] The applicant declares that the present invention illustrates the process method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned process steps, that is, it does not mean that the present invention must rely on the above-mentioned process steps to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the raw materials selected by the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A graphite negative electrode composite material with a core-shell structure, characterized in that: The graphite negative electrode composite material comprises porous graphite doped with a conductive carbon material and a coating layer located on the surface thereof; The coating layer comprises a porous oxide layer; the porous oxide layer is a porous aluminum oxide layer; The porosity of the coating layer is 5-30%; Taking the total mass of the graphite negative electrode composite material as 100%, the mass percentage of the coating layer is 1-10%.

2. The graphite negative electrode composite material according to claim 1, characterized in that: Taking the total mass of the graphite negative electrode composite material as 100%, the mass percentage of the coating layer is 2-3%.

3. The graphite negative electrode composite material according to claim 1, characterized in that: The conductive carbon material includes carbon nanotubes, conductive carbon black or graphene.

4. The graphite negative electrode composite material according to claim 1, characterized in that: Taking the total mass of the graphite negative electrode composite material as 100%, the mass percentage of the conductive carbon material is 1-10%.

5. The graphite negative electrode composite material according to claim 4, characterized in that: Taking the total mass of the graphite negative electrode composite material as 100%, the mass percentage of the conductive carbon material is 1.5-2.5%.

6. The graphite negative electrode composite material according to claim 1, characterized in that: The porosity of the coating layer is 15-25%.

7. A method for preparing the graphite negative electrode composite material according to any one of claims 1 to 6, characterized in that: The method comprises the following steps: (1) mixing a graphite negative electrode material and an oxidant, and drying to obtain a graphite negative electrode material A; (2) dispersing the graphite negative electrode material A obtained in step (1) and the catalyst solution, spray drying and crushing to obtain the graphite negative electrode material B; (3) calcining the graphite negative electrode material B and the carbon source to obtain porous graphite doped with a conductive carbon material, and then depositing a porous oxide on the surface of the porous graphite to obtain the graphite negative electrode composite material.

8. The method according to claim 7, characterized in that The graphite negative electrode material in step (1) includes any one of spherical natural graphite, flake graphite or artificial graphite, or a combination of at least two of them.

9. The method according to claim 7, characterized in that: The average particle size of the graphite negative electrode material in step (1) is 6-15 μm.

10. The method according to claim 7, characterized in that The oxidant in step (1) includes any one of nitric acid, sulfuric acid, potassium permanganate or hydrogen peroxide, or a combination of at least two of them.

11. The method according to claim 7, characterized in that The mass concentration of the oxidant in step (1) is 1-10%.

12. The method according to claim 7, characterized in that The mixing in step (1) is carried out under stirring.

13. The method according to claim 12, characterized in that The stirring temperature is 25-100°C.

14. The method according to claim 12, characterized in that The stirring time is 12-72h.

15. The method according to claim 7, characterized in that The drying step in step (1) includes a washing step with deionized water.

16. The method according to claim 7, characterized in that The catalyst in the catalyst solution in step (2) includes any one of ferric nitrate, nickel nitrate, cobalt nitrate, ferric chloride, nickel chloride or cobalt chloride, or a combination of at least two thereof.

17. The method according to claim 7, characterized in that The mass concentration of the catalyst solution in step (2) is 1-10%.

18. The method according to claim 7, characterized in that The mass ratio of the graphite negative electrode material A to the catalyst in step (2) is 100:(0.5-2).

19. The method according to claim 7, characterized in that The spray drying temperature in step (2) is 200-300°C.

20. The method according to claim 7, characterized in that The spray drying pressure in step (2) is 0.1-0.3 MPa.

21. The method according to claim 7, characterized in that The carbon source in step (3) includes any one of methane, acetylene, ethylene or ethane, or a combination of at least two of them.

22. The method according to claim 7, characterized in that The calcination in step (3) is carried out in an inert atmosphere.

23. The method according to claim 7, characterized in that The calcination temperature in step (3) is 700-1000°C.

24. The method according to claim 7, characterized in that The calcination time in step (3) is 1-6 hours.

25. The method according to claim 7, characterized in that The deposition in step (3) is atomic vapor deposition.

26. A lithium ion battery, characterized in that: The lithium-ion battery comprises a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, and the negative electrode sheet comprises the graphite negative electrode composite material according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • Anode active material hybridizing carbon nano fibers for lithium secondary battery

    CN101106192A

  • Lithium battery negative electrode material, preparation method thereof and lithium battery containing negative electrode material

    CN110165179A

  • Porous silicon-carbon composite material as well as preparation method and application thereof

    CN113675392A

  • Fast charge composite graphite material and preparation method thereof

    CN113764644A